THE EFFECT OF SATISFACTION AND TRUST ON THE LOYALTY OF CAR WASH CUSTOMERS OF LAMCINDO SURYA MAKMUR HYDRAULIC AUTOMOBILE COMPANY IN CIREBON CITY - Muhammad Nur Hari; Maidatul Khulwa; Dewi Melinda Fitri (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study aims to determine the effect of satisfaction and trust on customer loyalty in Lamcindo Surya Makmur Hydraulic Automobile Company in Wells Ribbon City. By employing a random sampling procedure, a sample of 100 respondents was chosen, and IBM SPSS 24 was used to analyze the data for validity, reliability, classical hypothesis testing, regression analysis, t-tests, and F-tests. The analysis' findings demonstrated a strong positive association between customer loyalty, trust, and satisfaction. Based on statistical research, customer loyalty is influenced by happiness and trust together in 20.9% of cases, with other factors not included in this study accounting for the remaining 79.1%. This indicates that retaining and raising customer satisfaction levels will be essential to bolstering patronage of Lamcindo Surya Makmur Hydraulic Automobile Company in Cirebon City.